Extinction of a cocaine‐taking context that protects against drug‐primed reinstatement is dependent on the metabotropic glutamate 5 receptor. (9th April 2014) - Kim, Jee Hyun; Perry, Christina; Luikinga, Sophia; Zbukvic, Isabel; Brown, Robyn M.; Lawrence, Andrew J.
Abstract We investigated the effects of extinguishing action‐reward versus context‐reward associations on drug‐primed reinstatement, and the potential role of the metabotropic glutamate 5 receptor (mGlu5) in these different types of extinction in rats that self‐administer cocaine. We observed that daily context extinction (non‐reinforced exposures to the cocaine‐taking context with retracted levers) was just as effective as daily lever extinction in reducing cocaine‐primed reinstatement compared with passive abstinence. Additionally, systemic injections of the mGlu5 negative allosteric modulator MTEP (3‐[(2‐methyl‐1, 3‐thiazol‐4‐yl)ethynyl]‐pyridine) following each extinction session significantly impaired the ability of context extinction to reduce cocaine‐primed reinstatement, without affecting reinstatement after lever extinction or passive abstinence.